Role of psychosocial work factors in the relation between becoming a caregiver and changes in health behaviour: results from the Whitehall II cohort study. Issue 12 (23rd May 2016) - Dich, Nadya; Head, Jenny; Hulvej Rod, Naja
Abstract : Background: The present study tested the effects of becoming a caregiver combined with adverse working conditions on changes in health behaviours. Methods: Participants were 5419 British civil servants from the Whitehall II cohort study who were not caregivers at baseline (phase 3, 1991–1994). Psychosocial work factors were assessed at baseline. Phase 4 questionnaire (1995–1996) was used to identify participants who became caregivers to an aged or disabled relative. Smoking, alcohol consumption and exercise were assessed at baseline and follow-up (phase 5, 1997–1999). Results: Those who became caregivers were more likely to increase frequency of alcohol consumption, but only if they also reported low decision latitude at work (OR= 1.65, 95% CI 1.15 to 2.37 compared with non-caregivers with average decision latitude), or belonged to low occupational social class (OR=2.38, 95% CI 1.17 to 4.78 compared with non-caregivers of high occupational social class). Caregivers were more likely to quit smoking if job demands were low (OR=2.92; 95% CI 1.07 to 7.92 compared with non-caregivers with low job demands), or if social support at work was high (OR=2.99, 95% CI 1.01 to 8.86 compared with caregivers with average social support). There was no effect of caregiving on reducing exercise below recommended number of hours per week, or on drinking above recommended number of units per week, regardless of working conditions. Conclusions: The findings underscore the importance of a well-balanced work environment as a resource for people exposed to increased family demands.